Recurrent Pustular Eruption Masquerading as Pustular Psoriasis in Netherton Syndrome. Issue 1 (2nd December 2014) - Mendiratta, Vibhu; Yadav, Pravesh; Chander, Ram; Aggarwal, Shilpi
Abstract We report a unique presentation of Netherton syndrome with recurrent pustular eruptions leading to an erroneous diagnosis of infantile pustular psoriasis. Light microscopy of eyebrow hair showed trichorrhexis invaginata, consistent with Netherton syndrome.